(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Why do researchers choose a Record Information System? Because the Barangay is using a log book or a manual process of recording information, researchers want to upgrade it into a computerized system to make their records a lot easier. The main goal of the researchers’ study is to develop a system that will alter the record-keeping method so as to supply economics. Moreover, the system is going to be ready to secure residents’ confidential records, to simply update residents’ profiles, and to provide backup information for all records. The main aim of creating the Barangay Record Information System is to provide an efficient and organized way for the barangay to manage and store resident information. The Barangay Record Information System was specifically designed to digitally store resident information in a secure and centralized database, allowing barangay officials to access and maintain records as needed without the limitations and inconvenience of traditional paper-based methods. This system presents various benefits by digitizing resident information and incorporating it into an all-inclusive database. It simplifies the process of data entry and retrieval while reducing the risk of errors, data loss, and inconsistencies that often arise from manual record-keeping methods. Additionally, the system features a user-friendly interface, enabling authorized personnel to easily manage and access resident records while ensuring the privacy and security of data. The Record Information System of Barangay Novaliches Proper will give safer storage of records and fast retrieval of files, maintain reliability and accuracy, and track files faster. This will be very useful to the staff, from handwritten records and manual issuing of barangay clearance and certificates, as well as the income and expense reports, to an automated processing system.